Surgical Versus Nonsurgical Treatment for Midshaft Clavicle Fractures in Patients Aged 16 Years and Older: A Systematic Review, Meta-analysis, and Comparison of Randomized Controlled Trials and Observational Studies. (July 2017) - Smeeing, Diederik P.J.; van der Ven, Denise J.C.; Hietbrink, Falco; Timmers, Tim K.; van Heijl, Mark; Kruyt, Moyo C.; Groenwold, Rolf H.H.; van der Meijden, Olivier A.J.; Houwert, Roderick M.
Background: There is no consensus on the choice of treatment of midshaft clavicle fractures (MCFs). Purpose: The aims of this systematic review and meta-analysis were (1) to compare fracture healing disorders and functional outcomes of surgical versus nonsurgical treatment of MCFs and (2) to compare effect estimates obtained from randomized controlled trials (RCTs) and observational studies. Study Design: Systematic review and meta-analysis. Methods: The PubMed/MEDLINE, Embase, CENTRAL, and CINAHL databases were searched for both RCTs and observational studies. Using the MINORS instrument, all included studies were assessed on their methodological quality. The primary outcome was a nonunion. Effects of surgical versus nonsurgical treatment were estimated using random-effects meta-analysis models. Results: A total of 20 studies were included, of which 8 were RCTs and 12 were observational studies including 1760 patients. Results were similar across the different study designs. A meta-analysis of 19 studies revealed that nonunions were significantly less common after surgical treatment than after nonsurgical treatment (odds ratio [OR], 0.18 [95% CI, 0.10-0.33]). The risk of malunions did not differ between surgical and nonsurgical treatment (OR, 0.38 [95% CI, 0.12-1.19]). Both the long-term Disabilities of the Arm, Shoulder and Hand (DASH) and Constant-Murley scores favored surgical treatment (DASH: mean difference [MD], −2.04 [95% CI, −3.56 to −0.52]; Constant-Murley: MD, 3.23 [95% CI, 1.52 to 4.95]). No differences were observed regarding revision surgery (OR, 0.85 [95% CI, 0.42-1.73]). Including only high-quality studies, both the number of malunions and days to return to work show significant differences in favor of surgical treatment (malunions: OR, 0.26 [95% CI, 0.07 to 0.92]; return to work: MD, −8.64 [95% CI, −16.22 to −1.05]). Conclusion: This meta-analysis of high-quality studies showed that surgical treatment of MCFs results in fewer nonunions, fewer malunions, and an accelerated return to work compared with nonsurgical treatment. A meta-analysis of surgical treatments need not be restricted to randomized trials, provided that the included observational studies are of high quality.